Multimedia's Impact on Education: A Study on the Teaching and Learning Process - Otho, Wakeel Ahmed; Iqbal, Samra; Ali, Shahbaz (Annals of Human and Social Sciences, 2024)
This study investigates the use of multimedia in improving the teaching and learning process in Pakistan. Information and communication technology has an impact on both student involvement and academic achievement. The study also investigates the possible obstacles and constraints of incorporating multimedia into Pakistan's education system. The findings of the study will be used to inform future policy decisions and educational practices in Pakistan's education system, ultimately aiming to improve academic performance.This study's evidence was gathered from primary sources, including staff and students from public and private educational institutions. The study's evidence was gathered from primary sources, including staff and students from public and private educational institutions, in order to ensure comprehensive and diverse data. The comprehensive and diverse data collected from these primary sources was crucial for the study's findings. Without this data, the study would not have been able to accurately analyze and draw conclusions.